(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The research aimed to reveal the social factors for juveniles to commit theft crimes in Syria. To achieve this goal, the research used the descriptive analytical method, a comprehensive social survey, for all members of the research community represented by juveniles present at the observation center in Lattakia and the Khalid bin Al-Walid Institute in Damascus, on charges of theft of various types. The research tool was applied, which is a measure of the social factors leading to juveniles committing theft crimes in Syria, prepared by the researcher. It was applied to all children present due to their small number and the ease of access to all of them. Their number reached (244) juveniles, distributed (55) juveniles at the observation center in Lattakia, and (189) juveniles at the Khalid bin Al-Walid Institute in Damascus. After obtaining the data, it was unloaded and analyzed using the SPSS program and reached a set of results, the most important of which were: The family plays the first and primary role in juveniles committing theft crimes, whether due to family disintegration, the absence of family supervision, or material or emotional deprivation and the surrounding influential circumstances such as poverty, unemployment, and the poor condition of the parents, followed by peer groups through imitating their behavior and being influenced by With them, and then comes the school, whether due to the absence of an attractive atmosphere for the child, or the absence of guidance to perform his roles correctly. At the end of the research, a set of proposals were presented that may help decision-makers or specialists in reducing juvenile delinquency and dealing with children in a sound manner that keeps them away from delinquency.